Changes in radon concentration in soils of the city of Tobolsk - Popova Elena (BIO Web of Conferences)
As part of this study, measurements of radon flux density were carried out, the average values of volumetric activity of radon from the soil surface in the foothill and upland parts of the city of Tobolsk (Tyumen region, Russia) were determined. Areas were selected that were evenly distributed within the city limits, and coordinates (latitude, longitude) were determined. As a result of the work, it was established that in 56% of the studied areas of the city of Tobolsk, the radon-222 flux density does not pose a danger to the population, the studied areas correspond to the first class, 44% – the second class of radon hazard. According to the soil classification in the study areas, 37.5% is sand, 31.25% is sandy clay, 18.75% is loam sand, and 12.5% is loam. It was found that high concentrations of radon-222 also depend on the granulometric composition of the soils studied.